1988
DOI: 10.1002/pola.1988.080260120
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of polymers using a windowless energy‐dispersive X‐ray detector

Abstract: The surface compositions of various polymeric films, grown electrochemically on platinum foils, have been investigated by energy‐dispersive x‐ray analysis in conjunction with scanning electron microscopy (SEM/EDS). Comparison of the relative area ratios of peaks for the C and N Kemission lines show that the EDS may be used to study the surface composition of polymers. The evidence presented strongly suggests that there is limited structural degradation and the elemental composition is not changed under the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We found only a few reports about the electrochemical polymerization of pyridylamine. [3][4][5] Very few studies on the chemical polymerization of pyridylamine have been reported. 6 Particularly, no report concerning the copolymerization of pyridylamine with aniline (AN) has been found hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…We found only a few reports about the electrochemical polymerization of pyridylamine. [3][4][5] Very few studies on the chemical polymerization of pyridylamine have been reported. 6 Particularly, no report concerning the copolymerization of pyridylamine with aniline (AN) has been found hitherto.…”
Section: Introductionmentioning
confidence: 99%